RNA INTERFERENCE IN DENTISTRY: A CRITICAL REVIEW - SONIKA GUPTA,; MUKESH SHARMA,; UMA BHARDWAJ, (International Journal of Pharma and Bio Sciences, 2016)
RNA interference (RNAi) is emerging as a promising technology in dentistry. This paper focuses on the applications and future prospects of RNAi, which opens new horizons in the diagnosis and treatment of dental diseases. RNA interference shows potential as a new and effective method of gene silencing that can selectively target and shut off the post-transcriptional expression of mRNAs. Thus, RNAi may play a big role in dental therapeutics because of its potential to modulate tissue regeneration, bone resorption, oral cancer development, tooth repositioning, and insurgence of craniofacial deformities. This paper updates the current knowledge and future aspects of RNAi in the field of dentistry.